(untitled) (Bangladesh Journal of Medicine, 2015)
Background: Frequency of transfusion transmitted diseases is unknown among tribal population of Rangamati. This study was undertaken to obtain data about burden of transfusion related diseases among tribal voluntary blood donors in Rangamati and to observe if there was any significant risk associated with ethnicity. The result expected to help identify health problems requiring urgent attention among tribal ethnic groups of Rangamati. Methods: A retrospective study was done in Rangamati General Hospital, Bangladesh where screening records of tribal voluntary blood donors from year 2005 to 2012 were scrutinized for seropositivity for hepatitis B & C, HIV, Syphilis and malaria infection. Frequency of these five diseases recorded . Results: Ninety six (3.81%) samples were positive for transfusion transmitted disease out of 2517 samples screened. Hepatitis B with 87 positive samples ranks highest. Frequency of seropositivity for HBsAg was 3.46%. Seropositivity of other diseases was Hepatitis C (0.28%), syphilis (0.04%) and malaria (0.04%). No samples were positive for HIV infection. Conclusion: Hepatitis B infection is the commonest transfusion transmitted disease among tribal population of Rangamati. Bangladesh J Medicine Jul 2014; 25 (2) : 52-54